2011
DOI: 10.1007/s00436-011-2591-1
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of lignans from Phryma leptostachya L. against Culex pipiens pallens

Abstract: The larvicidal activity of crude petroleum ether, ethyl acetate, and methanol extracts of the whole plants of Phryma leptostachya L. was assayed for its toxicity against the early fourth instar larvae of Culex pipiens pallens. The larval mortality was observed after 24 h of exposure. Among three solvent extracts from Phyrma leptostachya L., the petroleum ether extract exhibited the best larvicidal activity. The corresponding LC₅₀ values of petroleum ether, ethyl acetate, and methanol extracts were 3.23, 5.23, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The extracts of Amyris balsamifera , Daucus carota and Pogostemon cablin showed 100% larvicidal activities against C. pipiens pallens at 100 ppm (Park & Park, ). The LC 50 of the methanolic extract of Phryma leptostachya L. was 61.86 ppm (Xiao, Hu, Shi, Wei, & Wu, ). While Ali, Wang, and Khan () reported the LC 50 values of C. longa rhizome extract against A. aegypti and Anopheles quadrimaculatus were 38.2 and 7.5 ppm, respectively, Madhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of Amyris balsamifera , Daucus carota and Pogostemon cablin showed 100% larvicidal activities against C. pipiens pallens at 100 ppm (Park & Park, ). The LC 50 of the methanolic extract of Phryma leptostachya L. was 61.86 ppm (Xiao, Hu, Shi, Wei, & Wu, ). While Ali, Wang, and Khan () reported the LC 50 values of C. longa rhizome extract against A. aegypti and Anopheles quadrimaculatus were 38.2 and 7.5 ppm, respectively, Madhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding LC 50 values of petroleum ether, ethyl acetate, and methanol extracts were 3.23, 5.23, and 61.86 mg/L against the early fourth instar larvae of Cx. pipiens pallens [23] . Thanigaivel et al reported that the larvicidal activity of methanolic fractions from Adhatoda vasica leaf extracts were investigated against the Bancroftian filariasis vector Cx.…”
Section: Discussionmentioning
confidence: 99%
“…As part of an ongoing effort to identify potential pesticide molecules derived from natural products it was shown that lignans including Haedoxane A, Phrymarolin B and Phrymarolins I are the main active components of P. leptostachya L. (Figure 1) [810]. In our previous study [11–13], we found that some of the C-11 ether derivatives and dehydroxy Phrymarolin showed much higher activity than Phrymarolins I. We were interested in making analogues with a triazole substituent linked to C-11, since triazole is a common group to a well-known class of pesticides.…”
Section: Introductionmentioning
confidence: 99%